Options for improving the yield and nutritive value of maize and grain legume residues for ruminants in East African farming systems - Dejene, M. (University of Queensland, 2018)
The role and importance of livestock in smallholder crop-livestock systems and the importance of crop residues (CR) as ruminant feedstuffs in such systems are well established. The effects of genotype (G), environment (E) and crop management (M) factors on yields of grain and CR and the nutritive value of the CR of maize (Zea mays) and common bean (Phaseolus vulgaris) were investigated in an East African context. Genotype effects were examined in early and medium maturing (EM and MM, respectively) maize hybrids and popular varieties of common bean. Environment was examined at three sites for maize in the 2013 and 2014 cropping seasons and at four sites for common bean in 2013. Management effects examined were plant density (D) (5 and 7 plants/m2), height of cutting at harvest in maize, and harvest at early and final seed maturity in common bean. Quality attributes (nitrogen (N), neutral detergent fibre (NDF) and acid detergent fibre (ADF) contents and dry matter digestibility (DMD)) were analysed using near infrared spectroscopy (NIRS) and calibrations expanded and validated with reference samples of CR representing the experimental sample set.